Pengaruh Nilai Ekspor Besi Baja Indonesia Ke 10 Negara Tujuan - Frisca Yunita Sari; Betty Silfia Ayu Utami (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
Iron & Steel is the third leading commodity after CPO and coal in Indonesia. The purpose of this study is to analyze competitiveness and the factors that influence the value of Indonesian steel exports to 10 destination countries using a gravity model. The method of analysis of this research is quantitative with the analytical technique used is RCA to analyze competitiveness and the gravity panel data model to analyze the factors that influence Indonesia's iron and steel exports. The data used in analyzing is secondary data for the annual period obtained from the World Bank, the Central Bureau of Statistics, Uncomtrade, IMF, CEPII. The results of the data analysis show that the average Indonesian steel commodity shows an RCA value of < 1, which means that the Indonesian steel commodity is not yet highly competitive. Meanwhile, the variables GDP per capita, price, and distance to importing countries in the gravity data panel model affect the value of Indonesia's iron and steel exports by showing a probability of <0.5. In contrast to the variables of inflation, exchange rate, and production of the importing country in the gravity data panel model, they do not affect the value of Indonesia's iron and steel exports by indicating a probability of > 0.5.